2018
DOI: 10.7759/cureus.2756
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Beverages and Dietary Sodas Impact on Brain Health: A Mini Literature Review

Abstract: Sugar-sweetened beverages containing caffeine are widely used among humans nowadays and can have negative consequences on the overall health. Our study aims to discuss the effects of these sugar-sweetened beverages (SSB) and how they can impact the health in different ways particularly on the brain. Some of the mechanisms by which soft drinks can exert adverse effects include an increase in glutathione-6-dehydrogenase level, increased levels of gamma-aminobutyric acid (GABA), glutamate and dopamine alteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
0
18
0
3
Order By: Relevance
“…Por outro lado, ele realizou a mudança sugerida na dieta e elevou a quantidade de horas de sono, uma vez que estas mudanças podem diminuir os níveis de cortisol e, consequentemente, o estresse. 31 Alguns mecanismos pelos quais alimentos com grande quantidade de açúcares podem exercer efeitos adversos são devidos ao aumento no nível de glutationa-6desidrogenase, de ácido gama-aminobutírico (GABA), glutamato e alteração da dopamina nas ondas cerebrais. Assim, eles podem aumentar o estresse oxidativo nas células cerebrais por uma diminuição da monoamina oxidase e acetilcolina, a qual influência também a qualidade e a duração do sono.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Por outro lado, ele realizou a mudança sugerida na dieta e elevou a quantidade de horas de sono, uma vez que estas mudanças podem diminuir os níveis de cortisol e, consequentemente, o estresse. 31 Alguns mecanismos pelos quais alimentos com grande quantidade de açúcares podem exercer efeitos adversos são devidos ao aumento no nível de glutationa-6desidrogenase, de ácido gama-aminobutírico (GABA), glutamato e alteração da dopamina nas ondas cerebrais. Assim, eles podem aumentar o estresse oxidativo nas células cerebrais por uma diminuição da monoamina oxidase e acetilcolina, a qual influência também a qualidade e a duração do sono.…”
Section: Discussionunclassified
“…Assim, eles podem aumentar o estresse oxidativo nas células cerebrais por uma diminuição da monoamina oxidase e acetilcolina, a qual influência também a qualidade e a duração do sono. 31 De forma semelhante, deficiências de vitaminas do complexo B, A e -principalmente -C são apontadas como importantes para a patogênese da GUN por afetar o ciclo celular de células do epitélio, síntese de colágeno e a atividade fagocítica das células de defesa. 1 Desta forma, o conhecimento e controle destes fatores deve ser levado em consideração durante a formulação do plano de tratamento.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Recent studies suggest that ADHD is polygenic, and a variety of genes contribute to the development of the disorder. At the neurochemical level, both dopamine and norepinephrine are implicated with pharmaceutical intervention targeting these neurotransmitters [5] . Executive function occurs in the prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Higher SSB intake has also been associated with increased risk of chronic kidney disease and non-alcoholic fatty liver disease (Cheungpasitporn et al, 2014;Wijarnpreecha, Thongprayoon, Edmonds, & Cheungpasitporn, 2016). Importantly, recent research has found SSB intake negatively impacts cognitive function and brain health (Anjum, Jaffery, Fayyaz, Wajid, & Ans, 2018). Burger (2017) found that regular SSB consumption decreased neural response during SSB intake and increased emotional stimuli while looking at a SSB logo.…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%